RESEARCH PRODUCTIVITY AND IMPACT OF ASIAN COUNTRIES AND UNIVERSITIES IN THE FIELD OF ENERGY AND FUEL - Narongrit, Sombatsompop; Teerasak, Markpin; Preeyanuch, Ratchatahirun; Wutthisit, Yochai; Santi, Ittiritmeechai; Nongyao, Premkamolnetr; Chatree, Wongkaew (Malaysian Journal of Library and Information Science, 2017)
The research performances for Association of Southeast Asian Nations (ASEAN) countries and universities in the energy and fuel field were assessed using the standard bibliometric indicators proposed by the Centre for Science and Technology, University of Leiden, The Netherlands; and hindex, all the data being retrieved from the Web of Science (WoS) database during 2003-2009. The results suggested that Thailand had the highest number of published articles while Singapore was positioned first as concerns total citations and citations per publication. All the selected ASEAN countries seemed to publish their research works in a similar group of energy and fuel journals, while 15-50% of the published articles for the ASEAN universities had never been cited after publication. The research performance of Singapore was found to exceed the worldwide average reference while those of Malaysia, Thailand and Vietnam were just about average; those for the rest of the ASEAN countries were positioned below. At the university level, Nanyang Technology University (Singapore), National University of Singapore (Singapore) and King Mongkut’s University of Technology Thonburi (Thailand) were the top three ASEAN universities with the highest publication volumes, total citations and h-index values. The variations in h-index values for ASEAN universities most correlated with those in total citations. There was no apparent relationship between the h-index and ratio of citation/article to average field citation score (CPP/FCSm) values observed in this work. In conclusion, the research performances of ASEAN countries and their selected universities have now been revealed and discussed for the first time in relation to worldwide references.